NEUROPSYCHOLOGICAL PREDICTORS OF TREATMENT RESPONSE TO COGNITIVE BEHAVIORAL GROUP THERAPY IN OBSESSIVE–COMPULSIVE DISORDER. Issue 9 (21st April 2016) - Braga, Daniela T.; Abramovitch, Amitai; Fontenelle, Leonardo F.; Ferrão, Ygor A.; Gomes, Juliana B.; Vivan, Analise S.; Ecker, Kimberly K.; Bortoncello, Cristiane F.; Mittelman, Andrew; Miguel, Euripides C.; Trentini, Clarissa M.; Cordioli, Aristides V.
Abstract : Background: The available research on the relationship between neuropsychological functioning and the therapeutic outcome of obsessive–compulsive disorder (OCD) has yielded inconsistent results. In this study, our aim was twofold. First, we sought to evaluate the effects of cognitive behavioral group therapy (CBGT) on neurocognitive functions in OCD patients. Second, we assessed the viability of neuropsychological test performance as a predictor of treatment response to CBGT. Methods: One hundred fifty carefully screened OCD patients were randomized to receive either 12‐week CBGT ( n = 75) or to remain on a waiting list (WL; n = 75) for the corresponding time. Forty‐seven participants dropped out of the study, leaving 103 participants that were included in the analysis (CBGT, n = 61; WL, n = 42). Participants had several neuropsychological domains evaluated both at baseline and at end‐point. Results: A significant difference in obsessive–compulsive, anxiety, and depression symptoms was observed between treated patients and controls favoring the CBGT group, but no significant differences were found on neuropsychological measures after 3 months of CBGT. In addition, there were no differences between treatment responders and nonresponders on all neuropsychological outcome measures. Employing a conservative alpha, neuropsychological test performance did not predict CBGT treatment response. Conclusions: Although the CBGT group demonstrated significant improvement in OCD symptoms, no significant difference was found on all neuropsychological domains, and test performance did not predict treatment response.